Prologue (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
Late in life, architects seem more prone than other people to a particular form of compulsive disorder: the neurotic need to write a book. And not just a book, but The Book, the final book that explains everything, the validation of a life-work. How, after all, will the world get on with things unless they know what I know? It is an obligation – the polemical/memoir/monograph – that summarizes the thoughts and works of a lifetimeAt home I have a special shelf for such books, mostly written by friends or colleagues in their late seventies or later. Some of these volumes contain interesting ideas, most contain beautiful or at least worthwhile projects. But with very few exceptions, they are awful books. For whatever cathartic, or therapeutic service they may be to the authors, most of them are terrible to read.Often these books are only half-hearted attempts to enter the great library of the world’s ideas. The real motivation is just to make a book – a bunch of pages with a book cover and a binding, a title and the author’s name. The existence of the artifact is the main thing; whether anybody buys it, reads it, let alone likes it, are secondary matters. If one succeeds in making a book, it goes on bookshelves next to all the other books, all the other books, including the great ones. You don’t have to write a great book to be on the shelf with great ones – just a book. From a distance they all look pretty much the same. And all the authors are authors. Everybody knows the game, accepts it for what it is, and doesn’t read too critically. If things go well, there is even a cocktail party or two to celebrate the author.I cannot claim that Housing and the City, LOVE versus HOPE (Schiffer Publishing, 2018) is not a manifestation of this common mental disorder, but something weird has happened to it, something I can explain best in terms I learned during my mostly unsuccessful career as a football player. A book on a bookshelf is like sitting on the bench. Most guys who play, like most books, rarely if ever get in a game. They go through the rigors of training camp and daily practice, even the rituals of game day: the taped ankles, lamp-black under the eyes (fierce looking), and the fetish that many coaches have for new white shoe-laces every game day. But they almost never get in the game; they sit on the bench like books on a bookshelf, maybe read once or twice, but not the subject of weighty discourse.Every boy who plays football dreams of getting to the NFL – at least to the bench. There one could sit between the two-hundred-eighty-pound bruisers who spend half their lives in the weight room, and the sleek black guys with cool names like Darnell Savage or Tarvarious Moore. Suit-up; be one of the guys.I fully expected that Housing and the City, LOVE versus HOPE had the bench-warmer, bookshelf destiny ahead of it. Then my dear friends Lucio Barbera and Anna Del Monaco had the incredible idea for this volume – a dozen or two first-rate critics commenting on the book and taking on its argument. Good God – the football analogy is clear: the coach turns toward the bench and calls my name. He says, “Get in there, and tell Skip (quarterbacks always seem to have names like “Skip”) to call 47 cross-buck.47 cross-buck! That’s my play; I carry the ball! 4 back takes a one-count stutter-step to the right, cuts left, follows the pulling guard and explodes through the 7 gap to glory. Except half the time I tried it in practice, I was half a count late, the 7 gap had turned into a solid wall of flesh and I was smeared for a loss. No glory – quite the contrary.Those were the excruciating memories that flooded my brain as this extraordinary group of architects, teachers and thinkers agreed with stunning generosity to contribute to this volume. I was not to be sitting on the bench next to the bruisers, but on the field banging heads with them. Terrifying.As it has turned out, the bruisers are a bunch of sweethearts, incredibly indulgent and kind to me, despite their obvious critical talents and splendid prose. Kind, but not sappy. Some of them, most notably Ben Grant and Robert Campbell pose challenges to LOVE versus HOPE that will take a long time and much thought to answer. But I must thank Anna, Lucio and this amazing group for getting me off the bench and into the game. It is as thrilling as I dreamt it would be.